Nothing goes to waste : sustainable practices of re-use among indigenous groups in the Russian North - Siragusa, Laura; Arzyutov, Dmitry (Current Opinion in Environmental Sustainability, 2020)
In the last few decades, the literature on waste has soared and taken two main directions. Considering the assumption that waste is a natural category, which we need to 'dispose of', the scholarship on waste management and its sustainability offers mainly problem-solving propositions (e.g., the 3Rs proposalre-cycling, re-using, and reducing-or 'circular economy'). The social scientific waste studies literature takes a more critical stance from its outset and advances a relational account of waste. We aim to bring those two main research streams into dialogue through a presentation of two case studies among indigenous communities in the Russian North. Not only we disclose the hidden biases of the notion of circular economy and other 'innovative' problem-solving practices in the waste management literature, but we also propose to pay more attention to non-hegemonic waste practices amongst communities, which are often overlooked in both the waste management and the social studies of waste literature. Peer reviewed